Identification of novel Mycobacterium tuberculosis CD4 T-cell antigens via high throughput proteome screening. Issue 3 (May 2015) - Nayak, Kaustuv; Jing, Lichen; Russell, Ronnie M.; Davies, D. Huw; Hermanson, Gary; Molina, Douglas M.; Liang, Xiaowu; Sherman, David R.; Kwok, William W.; Yang, Junbao; Kenneth, John; Ahamed, Syed F.; et al.
Summary Elicitation of CD4 IFN-gamma T cell responses to Mycobacterium tuberculosis (MTB) is a rational vaccine strategy to prevent clinical tuberculosis. Diagnosis of MTB infection is based on T-cell immune memory to MTB antigens. The MTB proteome contains over four thousand open reading frames (ORFs). We conducted a pilot antigen identification study using 164 MTB proteins and MTB-specific T-cells expanded in vitro from 12 persons with latent MTB infection. Enrichment of MTB-reactive T-cells from PBMC used cell sorting or an alternate system compatible with limited resources. MTB proteins were used as single antigens or combinatorial matrices in proliferation and cytokine secretion readouts. Overall, our study found that 44 MTB proteins were antigenic, including 27 not previously characterized as CD4 T-cell antigens. Antigen truncation, peptide, NTM homology, and HLA class II tetramer studies confirmed malate synthase G (encoded by gene Rv1837) as a CD4 T-cell antigen. This simple, scalable system has potential utility for the identification of candidate MTB vaccine and biomarker antigens.